2020
DOI: 10.1017/s1368980020003808
|View full text |Cite
|
Sign up to set email alerts
|

Meal and snack patterns of 7–13-year-old schoolchildren in southern Brazil

Abstract: Objective: The aim of the current study was to identify and describe the meal and snack patterns (breakfast, mid-morning snack, lunch, mid-afternoon snack, dinner and evening snack) of public schoolchildren. Design: Cross-sectional study. Information on the previous day’s food intake was obtained through the Web-CAAFE (Food Intake and Physical Activity of Schoolchildren), an interactive questionnaire, which divides daily food consumption into three meals (breakfast, lunch and dinner) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…The description of the Web-CAAFE study design and sampling procedure has been published previously [ 17 , 18 ]. In brief, for the 2013–2015 surveys, primary sampling units were eligible classrooms (2nd to 5th grades) which were randomly selected from the complete list of schools with computer rooms (34 out of 37 schools with 6227 students enrolled in 2013; 34 out of 36 schools with 6500 students in 2014; 35 out of 36 schools with 7104 students in 2015) [ 17 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The description of the Web-CAAFE study design and sampling procedure has been published previously [ 17 , 18 ]. In brief, for the 2013–2015 surveys, primary sampling units were eligible classrooms (2nd to 5th grades) which were randomly selected from the complete list of schools with computer rooms (34 out of 37 schools with 6227 students enrolled in 2013; 34 out of 36 schools with 6500 students in 2014; 35 out of 36 schools with 7104 students in 2015) [ 17 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the 2017 survey, all public schools serving the 2nd to 5th grades with a computer room were considered eligible (19 schools), representing the five geographical regions of the city. Nine schools were randomly selected with 2333 students enrolled [ 18 ]. All students from 2nd to 5th grades were invited to participate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A Brazilian crosssectional study identified MPs and SPs in children aged 7-13 years using factor analysis, showing that breakfast, lunch and dinner patterns were characterised by traditional Brazilian foods (e.g. bread, cheese, processed meats, coffee with milk, rice, beans and beef/ poultry); however, the patterns consisting of fast foods and soft beverages were also observed, mainly for the evening snack (Cezimbra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%